Rule technologies : research, tools, and applications : 10th International Symposium, RuleML 2016, Stony Brook, NY, USA, July 6-9, 2016. Proceedings /: research, tools, and applications : 10th International Symposium, RuleML 2016, Stony Brook, NY, USA, July 6-9, 2016. Proceedings. (2016) - Unknown
No abstract available